Princeps' fury - Butcher, Jim, 1971- (Butcher, Jim, 1971- Codex Alera, 2008)
Tavi of Calderon, now recognized as Princeps Gaius Octavian and heir to the crown, has achieved a fragile alliance with Aleraas oldest foes, the savage Canim. But when Tavi and his legions guide the Canim safely to their lands, his worst fears are realized.